Odpowiedzi

2010-04-13T19:57:27+02:00
A) b:
a = b + c /- c
b = a-c
c:
a = b+c /-b
c = a-b

b) b:
a= bc - d /+d
bc = a+d /:c
b = (a+d):c
c:
a= bc - d /+d
bc = a+d /:b
c = (a+d):b
d:
a= bc - d /+d
a+d = bc /-a
d = bc -a

c) b:
a= bc+d /-d
bc = a-d /:c
b = (a-d):c
c:
a= bc+d /-d
bc = a-d /:b
c = (a-d):b
d:
a= bc+d /-d
a-d = bc /-a
-d = bc - a /*(-1)
d = -bc +a

d) b:
a = b(c+d) /:(c+d)
b = a:(c+d)
c:
a = b(c+d) /:b
a/b = c+d /-d
c = a/b -d
d:
a = b(c+d) /:b
a/b = c+d /-c
d = a/b - c

e) b:
a= b+c:d /*d
ad = bd +c
ad - bd = c
d(a-b) = c /:d
a-b = c:d /-a
-b = c:d - a /* (-1)
b = -c/d +a
c:
a= b+c:d /*d
bd+c = ad /-bd
c = ad - bd
c = d(a-b)
d:
a= b+c:d /*d
ad = bd+c
ad-bd = c
d(a-b) = c /:(a-b)
d = c:(a-b)
f) b:
a = b-c:d /*d
ad = bd-c
ad-bd = c
d(a-b) = c /:d
a-b = c:d /-a
-b = c:d - a /*(-1)
b = -c:d + a
c:
a = b-c:d /*d
bd-c = ad
bd - ad = c
c = bd - ad
d:
a = b-c:d /*d
ad = bd-c
ad - bd = -c
d(a-b) = -c /:(a-b)
d = -c:(a-b)

g) b:
a = b:c+d /*c
ac = b + cd
-b = cd - ac
-b = c(d-a) /*(-1)
b = -c(d-a)
c:
a = b:c+d /*c
ac = b + cd
ac - cd = b
c(a-d) = b /:(a-d)
c = b:(a-d)
d:
a = b:c+d /-d
a-d = b:c /-a
-d = b:c -a /*(-1)
d = -b:c +a

h) b:
a= b:c-d /+d
a+d = b:c /*c
b = c(a+d)
c:
a= b:c-d /*c
ac = b - cd
ac+cd = b
c(a+d) = b /:(a+d)
c = b:(a+d)
d:
a= b:c-d /+d
a+d = b:c /-a
d = b:c - a

i) b:
a= b:c + d /*c
ac = b +cd
b = cd - ac
b = c (d-a)
c:
a= b:c + d /*c
ac = b + cd
ac - cd = b
c(a-d) = b /:(a-d)
c = b:(a-d)
d:
a= b:c + d /-d
a-d = b:c /-a
-d = b:c -a /*(-1)
d = -b:c +a
39 3 39